2021
DOI: 10.1029/2019ea000968
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Reflectors Detected by SHARAD Reveal Stratigraphy and Buried Channels Over Central Elysium Planitia, Mars

Abstract: The interior morphology of Cerberus Fossae consists of a steep, layered upper slope and a gentler lower slope, which are presumably composed of exposed bedrock and talus, respectively (Plescia, 2003). Various landforms observed in this region have resulted in several hypotheses as to the origin of the Cerberus plains material, from a purely aqueous origin to a purely volcanic one. For example, Athabasca Valles is thought to have been carved by a high-discharge flood of water based on streamlined islands, notch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…This western extent of Marte Vallis was previously detected by Xiong et al. (2021). However, the channel is much shallower than the authors suggested due to the fact that valley is infilled by lava (permittivity of 7.8) and not ice‐rich material, which would have a permittivity of ∼3.…”
Section: Sharad Investigationsupporting
confidence: 81%
See 3 more Smart Citations
“…This western extent of Marte Vallis was previously detected by Xiong et al. (2021). However, the channel is much shallower than the authors suggested due to the fact that valley is infilled by lava (permittivity of 7.8) and not ice‐rich material, which would have a permittivity of ∼3.…”
Section: Sharad Investigationsupporting
confidence: 81%
“…Mapping out the extent of this reflector shows that it creates the interface of the lava flow to what is likely the underlying RV 1 unit, thus representing a large but shallow buried valley system visible in the subsurface DTM (Figure 10). This western extent of Marte Vallis was previously detected by Xiong et al (2021). However, the channel is much shallower than the authors suggested due to the fact that valley is infilled by lava (permittivity of 7.8) and not ice-rich material, which would have a permittivity of ∼3.…”
Section: Table 1 Continuedsupporting
confidence: 64%
See 2 more Smart Citations
“…Where possible, these CTX 3D products were co-registered to HRSC 3D products, where they had been publicly released [6]. Subsequently, very limited HiRISE DTM+ORI products [8], 35 HRSC image strips adjusted to MOLA DTM, covering the SPRC where available in the same season [9] and 82 HRSC and some 1,763 CTX stereo-pairs were processed covering the whole of the Valles Marineris area. This resulted in an 82-orbit HRSC mosaic where, in place of bundle block adjustment, a joint 3D point cloud and image co-registration using B-Spline fitting was performed to the reference MOLA DTM to eliminate both 3D shifts and high-frequency jitter effects, see previous section [3].…”
Section: Resultsmentioning
confidence: 99%